Development of a VideoScribe-Based Physics Learning Media Oriented Toward Conceptual Understanding of Momentum and Impulse - Nurhatina Nurhatina; A Hamid Rahman; Hermansyah Hermansyah (Indonesian Publication Center, 2022)
Low physics conceptual understanding among students is partly attributed to limited learning media variety, particularly in remote areas with restricted digital infrastructure. This study assessed the feasibility of and student responses to videoscribe-based physics learning media on momentum and impulse. A Research and Development (R&D) approach using the 4D model (Define, Design, Develop, Disseminate) was employed, limited to the Develop stage. Two expert validators evaluated the media, and a limited trial was conducted with 10 physics education students at a private university in Sumbawa Regency, West Nusa Tenggara, using a Likert scale instrument. The novelty lies in integrating videoscribe hand-drawn animations with momentum and impulse concepts into a single offline-accessible medium an approach unexplored in Indonesian higher education physics. Expert validation yielded an overall feasibility score of 76.44% (